Endoscopic Retrograde Cholangiopancreatography and Endoscopic Ultrasound: To Be One Traveler in Converging Roads - Moutinho-Ribeiro, Pedro (2018)
BACKGROUND: Endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) were initially introduced into the world of gastroenterology as purely diagnostic procedures. With progressive evolution of intervention, both these techniques conquered fields in the treatment of many conditions that had once been exclusively surgical domains. Nowadays, more and more clinical situations have an indication to perform both EUS and ERCP, and these two techniques are frequently required at the same time for the same patient. More than competitors, ERCP and EUS are truly complementary, with great ability for mutual aid. They share their main indications, equipment, accessories, and main technical gestures. OBJECTIVES AND METHODS: We review the major indications to perform both techniques, sequentially or complementarily, describe the common things that these two techniques essentially share, and discuss the ERCP-EUS single session. Also, the issues of learning curves and education of upcoming biliopancreatic endoscopists are highlighted. CONCLUSION: In recent years the complementation between ECRP and EUS has been growing both from a diagnostic and a therapeutic point of view, allowing optimization of the use of these techniques and the creation of a more systematized approach of patients with biliopancreatic pathology. Endoscopists with experience in both techniques will be increasingly important, suggesting a parallel formation in the training plans of future endoscopists with interest in the area.